Relating Ø/to/in the desert: Scottish World War II Poets in North Africa and the Middle-East - Stéphanie NOIRARD (E-REA)
“Relating” meaning both recounting and connecting, it is a suitable term to describe war literature which is, at the same time, aesthetic and testimonial. Scottish poets were sent to the African front during the Second World War and their poems, letters or diaries reflect their experience in Egypt, Libya and Tunisia, offering sharp contrasts with what is commonly believed or imagined of desert landscapes and the Desert War. The aim of this article is to examine how Scottish war poems may be inscribed in an artistic as well as a historical counter-discourse. The first part is a historical and cultural survey which contextualizes life and literary relationship in Cairo at the time, while evoking the main literary landmarks poets might have called up as they faced desert landscapes. The second part analyzes how they related to or broke away from these landmarks to relate their desert experience, with particular focus being set on the poem as a silent camera obscura. The last part turns to human landscapes and examines relationship within the 8th Army and the strong affinities Scottish poets felt towards German simple soldiers or North African civilians.